von Willebrand Factor, Soluble P-Selectin, Tissue Plasminogen Activator and Plasminogen Activator Inhibitor in Atherosclerosis - Blann, A D; Dobrotova, M; Kubisz, P; McCollum, C N (Thrombosis and Haemostasis, 1995)
Tissue plasminogen activator antigen (tPA), plasminogen activator inhibitor antigen (PAI-1), soluble P-selectin and von Willebrand factor antigen (vWf) were measured by ELISA in 41 patients with peripheral vascular disease (PVD), 41 with ischaemic heart disease (IHD) and in 46 age and sex matched asymptomatic controls. Increased vWf was found in patients with IHD (p = 0.0002) and in patients with PVD (p = 0.0011) relative to the controls but levels did not differ between the two patients groups. Raised tPA found in both PVD (p = 0.0006) and IHD (p = 0.0061) compared to the controls also failed to differentiate the two groups of patients. Soluble P-selectin was also raised in both groups (p = 0.003 in IHD and p = 0.0102 in PVD) with no difference between the groups. There were no differences in levels of PAI-1 between the groups. In the subjects taken as a whole, there were significant Spearman’s correlations between tPA and vWf (r = 0.37, p <0.001), tPA and triglycerides (r = 0.38, p <0.001), tPA and P-selectin (r = 0.19, p = 0.032), vWf and age (r = 0.25, p = 0.005) and inversely between vWf and HDL (r = -0.25, p = 0.006). These data support the concept that increased levels of tPA may be important in atherosclerosis, and indicate that soluble P-selectin may be useful in further analysis of the role of platelets and the endothelial cell in this disease.